Prevention of Prostate Tumor Development by Stimulation of Antitumor Immunity Using a Standardized Herbal Extract (Deep Immune®) in TRAMP Mice. (14th May 2018) - Liang, Peihe; Guo, Jia; Li, Shadan; Guan, Qiunong; Vanderheyden, Terry; So, Alan; Wang, Yuzhuo; Chen, Tao; Du, Caigan
Abstract : Low-risk prostate cancer (PCa) does not require immediate treatment, but PCa progression after years of active surveillance will need the treatment. This study was to test the efficacy of immunostimulant Deep Immune (DI) in controlling PCa progression. DI is an extract of eight different medicinal herbs. In vitro activity of DI was determined by phagocytosis activation using flow cytometric analysis of fluorescence-labeled latex bead uptake, expression of immune-modulating 84 genes using PCRarray, and tumor killing using coculturing with immune cells. Anti-PCa activity of DI in vivo was examined in male TRAMP mice. In vitro DI stimulated phagocytosis and expression of a panel of inflammatory mediators (C4b, CXCL3, lymphotoxin, NOS2, TLR1, TNF, and TNFSF14) in cultured macrophages and increased tumor killing of both macrophages and TRAMP mouse splenocytes. Daily intake of this herbal product significantly suppressed the tumor size (P = 0.0368 ) with lower histopathologic scores (P = 0.0364 ) in TRAMP mice, which were associated with an increase in both splenocyte cytotoxicity against tumor cells and numbers of CD8 T cells, macrophages, and dendritic cells in the spleens in vivo . In conclusion, daily intake of DI prevents PCa progression in TRAMP mice, suggesting the possible effectiveness of the immunostimulant herbal products on prevention of PCa progression after diagnosis of low-risk PCa.